DEVELOPMENT OF COURIER COMPANIES AS FOR THE E-COMMERCE MARKET SERVICE - Skowron-Grabowska, Beata; Sukiennik, Katarzyna; Szczepanik, Tomasz (Advanced Logistic Systems - Theory and Practice, 2016)
Increased manufacturing activity and rising demand for manufactured products reported by consumers require proper handling sale and purchase transactions and a flexible offer from companies offering transport services. Courier is a specialized company engaged in the handling of the contract starting from the receipt of the consignment from the sender to delivery to the person ordering, organizing with the smooth flow of information on the status of the consignment. The aim of the article is to present the relationship between the rapidly growing market of e-commerce and the development of the industry courier services. Courier services market is a rapidly growing industry dedicated services, the development of which is determined by the souped increasingly important e-commerce and the ability to handle the buying and selling of goods. The article presents the characteristics of the Polish market for courier services and discusses the service e-commerce market in Poland and in the European Union. Approximated and analysis the impact of the development of e-commerce and transaction services related to purchases via the Internet on the development of courier services.